2018
DOI: 10.1016/j.egypro.2018.04.084
|View full text |Cite
|
Sign up to set email alerts
|

Power and methanol production from biomass combined with solar and wind energy: analysis and comparison

Abstract: The purpose of this work is to investigate the feasibility of an integrated system consisting of biomass-based power generation built-in with carbon capture technology combined with a water electrolysis unit operated by solar cells and wind turbines to produce fuel through the methanol synthesis process. The configurations are examined both technically and economically to determine their feasibility, and subjected to sensitivity analysis to determine their economic viability and optimum performance. Each integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
2
Order By: Relevance
“…The initial investment, solar radiation, or wind potential and interest rate were the key factors for the variation in the technoeconomic performance of the systems for different locations. Among the three different test locations considered in the study, Beijing (China) was found to perform better economically compared to Denver (US) and Gotland (Sweden) (Firmansyah et al 2018). Rivarolo et al (2016) analysed the use of renewable energy (wind, hydro, and solar) for the methanol synthesis and studied the effects of different electricity costs (0.033-0.044-0.055 USD/kWh) as well as methanol market prices (441.40-551.75-662.10 USD/ton).…”
Section: Utilization Of Methanol With Renewable Energy Sourcesmentioning
confidence: 97%
See 1 more Smart Citation
“…The initial investment, solar radiation, or wind potential and interest rate were the key factors for the variation in the technoeconomic performance of the systems for different locations. Among the three different test locations considered in the study, Beijing (China) was found to perform better economically compared to Denver (US) and Gotland (Sweden) (Firmansyah et al 2018). Rivarolo et al (2016) analysed the use of renewable energy (wind, hydro, and solar) for the methanol synthesis and studied the effects of different electricity costs (0.033-0.044-0.055 USD/kWh) as well as methanol market prices (441.40-551.75-662.10 USD/ton).…”
Section: Utilization Of Methanol With Renewable Energy Sourcesmentioning
confidence: 97%
“…The plant reduced emissions by − 1.05 CO 2 e/kg methanol (Matzen et al 2015). Techno-economic analysis of a solar wind integrated power and methanol production process was studied by Firmansyah et al (2018). Because of the high initial cost of solar and wind systems, the proposed system could not compete economically with conventional power plants.…”
Section: Utilization Of Methanol With Renewable Energy Sourcesmentioning
confidence: 99%
“…Pemanfaatan energi angin dan matahari telah banyak dilakukan untuk berbagai keperluan. Referensi [7] menjelaskan produksi metanol dan energi listrik dengan atau tanpa menggunakan energi angin dan matahari. Analisis kelayakan teknik dan ekonomi digunakan untuk mengevaluasi kedua teknologi tersebut.…”
Section: Pengantarunclassified
“…To commercialize green MeOH production, the realization of MeOH parity (which is when green MeOH production cost is compared favorably with that of gray MeOH production) should be conducted. Hence, several studies dealing with techno-economic analysis (TEA) for green MeOH production have been reported to calculate the unit MeOH production cost at a certain point in time, as shown in Figure . …”
Section: Introductionmentioning
confidence: 99%